All options on the table : leaders, preventive war, and nuclear proliferation - Whitlark, Rachel Elizabeth (Cornell studies in security affairs., 2021)
"This book uses archivally based, comparative case studies to explore decision making regarding preventive war as a counterproliferation strategy by (1) US presidents Kennedy, Johnson, Bush 41, Clinton, and Bush 43 against China, Iraq, and North Korea and (2) Israeli prime ministers Begin, Rabin, and Olmert against Iraq, Pakistan, and Syria"--